Comparing the frequency of anemia in rheumatoid arthritis and axial spondyloarthritis patients and its relationship with hemogram parameters - Yilmaz, Ebru; Pasin, Özge (International Journal of Research in Medical Sciences, 2024)
Background: To compare the frequency of anemia in rheumatoid arthritis (RA) and radiographic axial spondyloarthritis (r-axSpA) patients and to investigate its relationship with hemogram parameters used as inflammation markers. Methods: The study included 87 RA patients and 116 r-axSpA patients. Characteristics of the patients, hemogram parameters (neutrophil-lymphocyte ratio ’NLR’, platelet-lymphocyte ratio ’PLR’, systemic immune-inflammation index ’SII’, red blood cell distribution width ’RDW’ and mean platelet volume ’MPV’), laboratory parameters (erythrocyte sedimentation rate ’ESR’ and C-reactive protein ’CRP’) and indices (Disease Activity Score in 28 Joints (DAS-28) for RA and the Bath Ankylosing Spondylitis (AS) Disease Activity Index (BASDAI) and AS Disease Activity Score with CRP (ASDAS-CRP) for axSpA) were recorded. Results: The mean age for RA and r-axSpA patients was 55.8±12.0 and 43.8±10.1 years. Anemia was present in 47.1% of RA patients and 31.9% of r-axSpA patients and more prominent in RA patients (p=0.030). There was a significant female gender superiority in those with anemia in r-axSpA patients (p<0.001). ESR, PLR, SII and RDW values were significantly higher in patients with anemia in the RA (p=0.002, p=0.048, p=0.035, p<0.001, respectively), whereas only ESR was significantly greater in patients with anemia in the r-axSpA (p=0.012). There was no significant difference between disease activity and anemia in both disease groups. Conclusions: Although the frequency of anemia was not affected by disease activity, female gender involvement was prominent. The increase in ESR and RDW values may reflect the possibility of developing anemia in rheumatic diseases.